Analisis Perkembangan Sosial-Emosional Tercapai dan Tidak Tercapai Siswa Usia Dasar - Muhammad Shaleh Assingkily; Mikyal Hardiyati (Al-Aulad: Journal of Islamic Primary Education, 2019)
This article aims to examine social-emotional development of the student's age. As for the formulation of a problem in this study i.e. (1) how the social-emotional development is achieved and not achieved grade IV MI Nurul Ummah in learning, (2) how the social-emotional development is achieved and not achieved grade IV MI Nurul Ummah outside of learning, and (3) how the efforts of teachers in developing social-emotional grade IV MI Nurul Ummah. This research used the qualitative approach with observations on the social-emotional development of grade IV MI Nurul Ummah. As for the results of this study suggest that (1) social-emotional development of students in learning that are achieved, i.e. students show an attitude of caring, participation, communication, interactive, teamwork, ability and showing confidence, While that is not achieved, i.e. quiet, it's hard to adapt, a closed, private, and difficult to communicate with people deems foreign.; (2) the social-emotional development of students outside the learning achieved, i.e. students show the attitude of empathy, caring, helpful friends, don't show the attitude of keakuan, and being able to control your emotions when interacting or play, while not achieved,i.e. play only with friends nearby, less concerned with what is happening around him, speaking only when needed, and enjoy learning more than play.; (3) efforts undertaken teacher in developing social-emotional students; sets the position of the seated students, giving the same attention to all students, and to give guidance to students in order to encourage the achievement of social- emotional development of children.Keywords: Analysis, Social-Emotional Development is Achieved and not Achieved